2007
DOI: 10.1158/1078-0432.ccr-06-1908
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib Prevents Neuroblastoma Tumor Development and Potentiates the Effect of Chemotherapeutic Drugs In vitro and In vivo

Abstract: Purpose: Neuroblastoma is the most common and deadly solid tumor of childhood. Cyclooxygenase-2 is expressed in clinical neuroblastoma tumors and cell lines and inhibitors of this enzyme induce apoptosis in human neuroblastoma cells in vitro and in neuroblastoma xenografts in vivo. We hypothesized that the cyclooxygenase-2^specific inhibitor celecoxib could enhance the cytotoxic effect of chemotherapeutic drugs currently used in neuroblastoma treatment. Furthermore, we investigated if prophylactic treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 43 publications
1
50
0
Order By: Relevance
“…Testing for synergistic or additive effects of combination therapy the data was done as described (Ponthan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing for synergistic or additive effects of combination therapy the data was done as described (Ponthan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As a secondary antibody, the HRP-SuperPicture Polymer detection kit and matched isotype controls were used (Zymed Laboratories Inc., San Francisco, CA, USA). Bandeirea simplifolica (BS-1; Sigma-Aldrich) lectin was used to highlight murine endothelial cells as described previously (Segerstrom et al, 2006;Ponthan et al, 2007). Proliferation and apoptosis (cleaved caspase-3) were quantified at  400 magnification, whereas microvessel density (BS-1) was quantified at  200.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…As a control for nonspecific background staining, sections were incubated with rabbit IgG isotype control (Zymed). Biotinylated Bandeiraea simplicifolia (BS-1, L3759; Sigma-Aldrich) lectin was used for highlighting endothelial cells as described previously (17). Apoptosis and proliferation were assessed by counting the number of positively stained nuclei and the total number of tumor cells in three representative regions in three tumors from each treatment group at Â400 magnification.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…We and others have reported that cyclooxygenase (COX) inhibitors induce cell death and enhance chemosensitivity in neuroblastoma (Johnsen et al, 2004;Lau et al, 2007;Ponthan et al, 2007). COX inhibitors are non-steroidal anti-inflammatory drugs commonly used as analgesics and anti-inflammatory agents, but have also been shown to have anticancer properties (Thun et al, 2002).…”
Section: Introductionmentioning
confidence: 99%